Controlled release of 5-fluorouracil and progesterone from magnetic nanoaggregates - Ragab DM (Dove Medical Press, 2012)
Doaa M Ragab,1 Sohrab Rohani,1 Styliani Consta21Department of Chemical and Biochemical Engineering, 2Department of Chemistry, The University of Western Ontario, London, Ontario, CanadaBackground: The potential use of magnetic nanoparticles in biomedical applications has witnessed an exponential growth in recent years.Methods: In this study, we used nanoaggregates of magnetic nanoparticles as carriers for controlled drug delivery. The nanoaggregates are formed due to the presence of the block copolymer of polyethylene oxide-polypropylene oxide (Pluronic F-68) and beta-cyclodextrin that surround the magnetic core of the nanoparticles. The administration of the drug carriers occurs by inhalation, and the drug is delivered systemically via the pulmonary route. We tested the delivery of 5-fluorouracil and progesterone, which are used as models of hydrophilic and hydrophobic drugs, respectively.Results: The estimated nanoaggregates' diameters are between 293 nm ± 14.65 nm and 90.2 nm ± 4.51 nm, respectively. In-situ and post-synthesis techniques are two approaches for drug loading. The polymer composition of nanoaggregates and initial drug concentration showed a significant effect on both the drug entrapment efficiency and release kinetics. Average drug entrapment efficiencies ranged between 16.11% and 83.25%. In-situ loaded samples showed significantly slower release rates. The drug release mechanism is investigated by mathematical curve fitting to different drug release kinetics models. In most cases, the Peppas model has shown good correlations (coefficients of correlation, R2, between 0.85 and 0.99) with the examined release profiles. The estimated release indices are below 0.5, which indicates the Fickian diffusion mechanism. For samples with an initial burst effect, the modified Peppas model can provide a better understanding of the drug release mechanism, both in the samples loaded with progesterone, or those high polymer concentrations.Conclusion: Our work showed prolonged delivery of drugs (5-fluorouracil and progesterone) by diffusion from nanoaggregates, with the potential to reduce dose-related adverse effects.Keywords: Nanoaggregates, 5-fluorouracil, progesterone, release kinetics, Fickian diffusion